Painless project management : a step-by-step guide for planning, executing, and managing projects - McGhee, Pamela, 1946- (John Wiley & Sons, 2007)
"Veteran project managers McGhee and McAliney present a comprehensive guide to effective project management, complete with real stories and case studies from actual project managers. The authors reveal how the complexity of project management is not in the process itself, but in the people and organizational relationships that must also be managed. They boil down the basics of project management so you can design a simple, effective plan for any project and follow it through to a successful completion."--Jacket